Global capital markets : integration, crisis, and growth - Obstfeld, Maurice; Taylor, Alan M. (Cambridge, UK ; New York : Cambridge University Press, 2004)
The book presents an economic survey of international capital mobility since the late 19th century. Theory and empirical evidence are used to evaluate the evolution of globalization in financial markets .
Includes bibliographical references (p. 315-348) and index.
opc 10/10/16
Loans
Keywords: International finance- history; Capital market - history; International economic relations - - history